The Effect of Maintenance and Repair on the Inventory of Spare Parts in Trucking Fleet Through Maintenance Costs in Transportation Companies - Rifki, Salman; Suraharta, I Made; Setiawan, Edhie Budi; Abidin, Zaenal; Artanti, Dian (Dinasti International Journal of Digital Business Management, 2025)
Land Transportation Radiation Activities is a transportation company located at Marunda Center Block A, North Jakarta. The company's main activity involves renting trucks for logistics operations across Indonesia. This research employs a quantitative research approach. The findings indicate that there is an influence of the maintenance variable on inventory, as the results show that the better the maintenance carried out, the more it minimizes the occurrence of further damage, which, in turn, affects the company's spare parts inventory. The study also found an influence of the repair variable on inventory, with the positive result showing that repairs require adequate inventory. There is an influence of the maintenance variable on servicing, as the results show that good repairs minimize the occurrence of more severe damage, which can impact inventory levels. However, there is no influence of the servicing variable on inventory, as the results show that servicing costs do not occur if maintenance and repairs are not performed. Furthermore, there is no influence of the repair variable on servicing, as the repair costs are absent when a company performs good maintenance. Additionally, there is no influence of maintenance on inventory through servicing, as field data processing indicates that maintenance does not occur according to the preventive maintenance schedule, due to a high number of orders and limited time for preventive maintenance. There is also no influence of repairs on inventory through servicing, as the results indicate that repairs are quite frequent due to the lack of scheduled preventive servicing.